Analisis Kehalalan Produk Makanan dalam Upaya Perlindungan Konsumen Bagi Umat Muslim: Studi Kasus Pasar Kiaracondong - Rahmawafi, Asy Syifa Cahya; Saepurohman, Muhammad (Ikatan Da'i Indonesia, 2024)
This study discusses the analysis of halal food products in an effort to protect consumers for Muslim in the Kiaracondong market. The objectives of this study are: 1) to further examine the halalness of food products as an effort to protect consumers in the Muslim community in Kiaracondong Market, Bandung City, West Java. 2) to find out the form of Muslim consumer protection in Kiaracondong Market, Bandung City, West Java. In running their business, most processed meat food traders do not fully understand the halal food products and consumer protection. This study used interview data collection techniques and documentation, interviews were conducted to traders of processed food products and consumers who purchased these food products. Documentation is used to obtain data regarding the description of Kiaracondong Market, Bandung City, West Java. Based on data analysis by conducting interviews and documentation at Kiaracondong Market, Bandung City, West Java, researchers can conclude that both food traders and consumers have not implemented halal product standards as an effort to protect consumers. This is due to the lack of understanding and knowledge as well as awareness of traders of sellers about halal food standards to ensure the protection of Muslim consumers.